2023
DOI: 10.3389/fimmu.2023.1097449
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge and vaccination intention for human papillomavirus on trans girls by their main caregiver: A cross-sectional study

Abstract: IntroductionTrans women are highly affected by the human papillomavirus (HPV) and are at risk of suffering from HPV-related diseases such as oropharyngeal, anal, penile, or neovaginal neoplasia. HPV vaccination seems to be a good strategy to reduce HPV-related diseases, mainly during the early age before the first sexual intercourse, but only cisgender girls are covered by the National Health Services, while some high-risk groups such as trans girls are not included. Achieving a high vaccination rate is import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…A systematic search was performed in four databases on 13 September 2023, resulting in 9322 articles; after removing the duplicates, 4206 publications were screened by title and abstract. In total, 133 were assessed for full-text, and 25 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] were included in the systematic review and meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic search was performed in four databases on 13 September 2023, resulting in 9322 articles; after removing the duplicates, 4206 publications were screened by title and abstract. In total, 133 were assessed for full-text, and 25 [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] were included in the systematic review and meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a lack of or insufficient knowledge about HPV (or the HPV vaccine) could discourage parents from vaccinating their children; other detrimental factors identified were valuing personal knowledge more than experts’ opinions and having a positive attitude toward social media stories or Internet-based information about the vaccine [ 22 , 25 , 28 , 29 , 30 , 32 , 39 ]. Five studies found no association between HPV knowledge (regarded as an STI), HPV vaccine knowledge or knowledge related to cervical cancer screening [ 19 , 22 , 26 , 37 , 40 ] and parents’ intention to vaccinate one child.…”
Section: Resultsmentioning
confidence: 99%